Nasal foreign bodies in children: kissing it better. Issue 9 (26th June 2010) - Taylor, Colleen; Acheson, Jonathan; Coats, Timothy J
Abstract : Objective: To evaluate the use, success rate and time in the paediatric emergency department when employing the kissing technique to remove nasal foreign bodies from children. Methods: The present work was a retrospective case note review for children attending with a nasal foreign body over a 15-month period. Results: In all, 116 children had a confirmed nasal foreign body and 84 were treated by the kissing technique with a success rate of 48.8%. This group had lower rates of instrumentation (20.2% vs 53.1%) and general anaesthesia (11.9% vs 18.8%). The average time saved per patient who had the kissing technique attempted in the paediatric emergency department was 30.6 min. Conclusion: The kissing technique should be employed as a preferred technique to remove nasal foreign bodies in children.